Colonial subjects : race and gender in french West Africa - Griffiths, Claire (International journal of sociology and social policy ;, 2006)
This e-book contains the first English translation of a unique report on women living under the colonial rule in West Africa. Denise Savineau's 'Report on Women and the Family in French West Africa' (1938), which is held in the National Archives of Senegal, highlights the French colonial social development agenda.